Outcomes after implementation of prophylactic protocol for venous thromboembolism in surgical patients: A retrospective cohort study - Kittitirapong N. (2023)
Introduction: Venous thromboembolism (VTE) in surgical patients is a preventable cause of hospital death. In previous studies, the prevalence of VTE decreased after implementing a prophylactic protocol. Because of the low rate of VTE prophylaxis in Thailand, we studied the outcomes after the implementation of a VTE prophylactic protocol in our hospital. Methods: A retrospective cohort single-center study was conducted from November 2019 to November 2020 in the Department of Surgery. We established the VTE prophylactic protocol using a multidisciplinary team approach and the Caprini score risk assessment model. The outcomes were the incidence of symptomatic VTE, VTE-related death, risk factors, and safety. Results: In total, 6983 patients were admitted to the surgical department during the study period. After excluding patients with current VTE and missing data, 4579 patients were enrolled in this study, and 1579 (34.5%) patients at high risk for VTE were identified. The use of pharmacological prophylaxis, mechanical prophylaxis, and early ambulation in the entire cohort was lower than that in high-risk patients (7.99%, 19.81%, and 21.56% vs. 15.77%, 31.10%, and 46.55%, respectively). In the comparison of before and after implementation, the prevalence of symptomatic VTE and 30-day mortality of VTE decreased from 1.20% to 0.37% and from 0.11% to 0.02%, respectively. No major bleeding occurred. Conclusions: After protocol implementation, the prevalence of symptomatic VTE and VTE-related death decreased. The VTE prophylaxis was safe. We highly recommended using a multidisciplinary team approach VTE prophylaxis in high-risk surgical patients.